Personality and Online Learning - Downing, Kevin; Yu, Baohua (INTI International University, 2011)
This paper provides a comparative evaluation of two pilot online courses with their traditionally taught counterparts in a University of Hong Kong with the purpose of Identifying particular characteristics of effective online learning. Students enrolled on two online courses were compared with their peers who were enrolled on the equivalent classroom based courses. Student satisfaction measures were taken from participants in both modes of delivery and compared with student learning style measured using the Honey and Mumford Learning Style Questionnaire. We find in this study that Extraversion/Introversion shows potential as a predictive measure of student satisfaction in online/blended learning modes of delivery, and Reflector Learning style is correlated with high reported student satisfaction. This study suggests that the traditional classroom-based Learning experience might not be as satisfying far Asian Reflectors as an online blended mode of delivery, and Western universities would be well-advised to consider this when planning programmes with an internationally diverse student population in mind.